Por uma abordagem diacrônica dos gêneros do discurso à luz da concepção de tradição discursiva: um estudo com editoriais de jornal - Zavam, Aurea Suely (2009)
The research tries to design, lato sensu, a methodology for genre analysis, which considers the continuous process of changings a genre undergoes in its evolutionary trajectory and, in stricto sensu, it aims to contribute with the reconstitution of a newspaper genre. In this sense, starting from surveys on newspapers in the state of Ceará from the 19th century to the present day, one proposed a theorical-methodological way framed under the perspective of the German Romance Philology, which allows identify traces of changing and traces of permanence. The choice for such methodology is explained for the belief in the discourse genre analysis, understood here as a discoursive tradition. Even under a synchronic approach, it must seek for the understanding of the phenomenon rescuing its trajectory in the language history in which it is materialized. From the bakhtinian concept of transmutation, which is underlying the proposed theoretical-methodological approach, a bidimensional analysis is carried out: the context and the text. In the first dimension one try to give account of the implicit aspects in the enunciative ritual: the socio-historical context in which the texts were produced as well as the participants involved in the interaction and their respective purposes. The second dimension aims at describing linguistic and discoursive traces and ultimately define the aspects linked to the form (diagramation and locus in the text), to the content (issue approached in the text, discoursive topic), and to the norm (linguistic mechanisms and discoursive strategies that are important and prominent). The analysis revealed that, in addition to continuing being characterized by aspects such as topography, communicative purpose and authorship, the editorial is a discoursive tradition that, despite its recognized stiffness, is shown open to the incorporation of the constituent elements of other genres, in this case, the news and the interview. It is believed, thus, that this research may contribute to the studies of an emerging area that little by little is becoming more and more popular among linguists: the philology of genres.